Emerging Paradigms in Insulin Resistance - Burke, Susan J. (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book provides a resource for the scientist or medical professional interested in the topic of insulin resistance. With a mix of review and primary data articles, emerging paradigms in insulin resistance are highlighted. The topics are succinctly presented, and distinct viewpoints are represented. An introduction to the Special Issue that provides summaries of the studies included, is provided by the Guest Editor, Dr. Susan Burke, and her colleague at the Pennington Biomedical Research Center, Dr. Jason Collier.